Blends of LNR with unsaturated polyester resin from recycled PET: comparison of mechanical properties and morphological analysis with the optimum blend by commercial resin - Siti Farhana Hisham; Ishak Ahmad; Rusli Daik; Anita Ramli (Universiti Kebangsaan Malaysia, 2011)
In this study, poly(ethylene terephthalate) (PET) wastes bottle was recycled by glycolysis process using ethylene glycol. The unsaturated polyester resin (UPR) was then prepared by reacting the glycolysed product with maleic anhydride. The blend of UPR based on recycled PET wastes with liquid natural rubber (LNR) was carried out by varying the amount of LNR from 0 to 7.5 wt%. Mechanical tests such as tensile and impact were conducted to investigate the effects of LNR on the mechanical properties. Scanning Electron Microscopy (SEM) was used to analyze the morphology of the breaking area resulted from the tensile tests on the UPR and blend samples. From the results, the blend of 2.5 wt% LNR in UPR based recycled PET wastes achieved the highest strength in the mechanical properties and showed a well dispersed of elastomer particles in the sample morphology compared to other blends concentrations. This blend sample was then compared to the optimum blend of LNR with commercial resin through the glass transition temperature value Tg, mechanical strength and morphology properties. The comparison study showed that the Tg for UPR based recycled PET was higher than the value represented from commercial resin due to the degree of crystalinity in the molecular structure of the materials. LNR was found to be an effective impact modifier which gave a greater improvement in UPR from recycled PET wastes structure but not to the commercial one which needs 5% LNR to achieve the optimum properties. Thus, the compatibility between the UP resin based recycled PET and LNR was much better than with the commercial resin